Relationship between all-cause mortality and triglyceride-glucose-body mass index in elderly patients with intravenous thrombolysis for acute ischemic stroke: a retrospective cohort study - Cheng, Yuan; Zhai, Mingfeng; Xie, Zhubiao (Frontiers in Neurology, 2026)
BackgroundTriglyceride-glucose-body mass index (TyG-BMI) has been shown to be a reliable surrogate for insulin resistance (IR), but the relationship between TyG-BMI and acute ischemic stroke (AIS) is unclear. In this study, we investigated the relationship between TyG-BMI and long-term all-cause mortality in elderly patients with intravenous thrombolysis for AIS.MethodsWe enrolled 452 elderly patients with acute ischemic stroke treated with intravenous thrombolysis with alteplase and divided them into four groups according to TyG-BMI quartiles, and the endpoint event of the study was all-cause death from AIS. The Kaplan–Meier (K-M) curve method was used to compare the outcomes among the groups, while multivariate Cox proportional risk regression models and restricted cubic spline (RCS) were utilized to explore the association between TyG-BMI and these outcomes. In addition, subgroup analyses were performed.ResultsA total of 452 elderly patients with intravenous thrombolysis for AIS were included, with a median age of 73.0 years, an interquartile range of 68.0–78.0 years, 58.4% males, a mean TyG-BMI of 205.54 ± 38.51. The follow-up period was more than six years, after which 75 (16.6%) patients died. K-M curve analysis demonstrated that patients with lower TyG-BMI levels had a higher risk of long-term all-cause mortality from AIS. When TyG-BMI was classified according to quartiles, Cox proportional risk regression analysis confirmed that both the Q1 group [HR, 3.482; 95% CI: 1.560–7.774; p = 0.002], Q3 group [HR,2.819; 95% CI: 1.196–6.640; p = 0.018] and the Q4 group [HR, 2.928; 95% CI: 1.259–6.806; p = 0.013] were associated with higher all-cause mortality rates, using the quartile with the lowest mortality as the reference. In addition, restricted cubic spline curves revealed a nonlinear relationship between TyG-BMI and long-term all-cause mortality (nonlinear p-value = 0.048).ConclusionIn this study, we found a U-shaped correlation between TyG-BMI and long-term all-cause mortality in elderly patients with AIS undergoing intravenous thrombolysis. TyG-BMI can be used as a predictor of all-cause mortality in this group of patients.